Gaps in knowledge about oral health and fluoride in two Ecuadorian communities: implications for caries and fluorosis prevention - Cedeño Mejia, Ingrid (2025)
Introduction: Dental caries remains one of the most prevalent pathologies worldwide, affecting the health, nutrition, and psychosocial well-being of the pediatric population. In Ecuador, its high incidence is associated with social inequalities and limited preventive strategies. Although the use of fluorides is an effective tool for its control, the lack of knowledge regarding their proper use has contributed to an increase in dental fluorosis, particularly in rural areas. Objective: To identify the knowledge, attitudes, and practices regarding oral health, fluorides, and dental fluorosis among parents of children aged 5 to 12 years in two Ecuadorian communities with distinct sociocultural characteristics. Materials and Methods: An observational, cross-sectional study was conducted in Salasaka and Cayambe, involving 183 parents selected through convenience sampling. A structured questionnaire was applied, addressing sociodemographic variables, knowledge, attitudes, oral hygiene practices, and fluoride use. Data were analyzed using descriptive statistics and non-parametric tests. Results:The highest proportion of participants demonstrated an intermediate level of knowledge and practices concerning oral health, with better outcomes in Salasaka. A significant relationship was identified between knowledge level and locality (p=0.000). However, no significant differences in knowledge about fluorides were found between communities, highlighting a generally low level of information. Conclusions:The study reveals significant deficiencies in fluoride-related knowledge in both communities, despite differences in general oral health knowledge. It is recommended to implement culturally adapted oral health education programs that include information on the safe use of fluorides and the prevention of dental fluorosis.